Non-destructive evaluation of microelectronic components - Chan, Kai Chong. (2008)
Popcorn package cracking in plastic IC packaging can be classified into three types: Type I referring to failure originating from delamination between the mold compound and die pad interface, Type II originating from the die attach region, and Type in originating from the interface between the mold compound and the silicon die. Recent advance in packaging design, process and materials such as mold compound have been effective in eliminating or reducing the occurrence of Type I and HI failures. However, Type II failures remain prevalent. The present work describes the results of a vigorous study to investigate the properties of various die attach materials that affect Type II popcorn cracking using a TQFP 208 package as a test vehicle. In addition, the work also reports the failure mechanism of Type II failure using SAM (scanning acoustic microscopy) as a failure analysis tool.